Understanding preclinical and clinical immunogenicity risks in novel biotherapeutics development - Sauna, Zuben E.; Jawa, Vibha; Balu-Iyer, Sathy; Chirmule, Narendra (Frontiers in Immunology, 2023)
Immunogenicity continues to pose a challenge in the development of biotherapeutics like conventional therapeutic-proteins and monoclonal antibodies as well as emerging modalities such as gene-therapy components, gene editing, and CAR T cells. The approval of any therapeutic is based on a benefit-risk evaluation. Most biotherapeutics address serious medical conditions where the standard of care has a poor outcome. Consequently, even if immunogenicity limits the utility of the therapeutic in a sub-set of patients, the benefit-risk assessment skews in favor of approval. Some cases resulted in the discontinuation of biotherapeutics due to immunogenicity during drug development processes, This special issue presents a platform for review articles offering a critical assessment of accumulated knowledge as well as novel findings related to nonclinical risks that extend our understanding of the immunogenicity of biotherapeutics. Some of the studies in this collection leveraged assays and methodologies refined over decades to support more clinically relevant biological samples. Others have applied rapidly advancing methodologies in pathway-specific analyses to immunogenicity. Similarly, the reviews address urgent issues such as the rapidly emerging cell and gene therapies which hold immense promise but could have limited reach as a significant number of the patient population could potentially not benefit due to immunogenicity. In addition to summarizing the work presented in this special issue we have endeavored to identify areas where additional studies are required to understand the risks of immunogenicity and develop appropriate mitigation strategies.